2020
DOI: 10.1016/j.gene.2019.144166
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inheritance and intergenerational effects in mollusks

Abstract: List of abbreviations 5mC5-methylcytosine, a cytosine that has been modified by the addition of a methyl group on its 5th carbon ADP Adenosine diphosphate AFLP Amplified fragment length polymorphism BLAST Basic Local Alignment Search Tool BS-Seq Bisulfite sequencing BS-PCR-Seq PCr amplification after bisulfite sequencing followed by sequencing Cd Cadium meDIP-seq Methylated DNA Immunoprecipitation sequencing MiRNAs Micro RNAs MSAP Methylation-sensitive amplified polymorphism MS-PCR Methylation-specific PCR pCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 150 publications
1
38
0
Order By: Relevance
“…A similar result was observed in mice, where only the gene expression patterns of female offspring were impacted by maternal exposure to predator-cues (St-Cyr and McGowan, 2015). Interestingly, Hales et al (2017) observed a decrease in the number of differentially expressed genes between the F1 and F2 generations-a trend consistent with the observed decrease in transgenerational responses ( §4.2; Walsh et al, 2015) and the lability of inherited epigenetic marks (Fallet et al, 2020). In a companion methodological paper, Schield et al (2016) found shifts in the methylation state of sampled loci between F0 (with predator-cues) and F1 (without predatorcues) in D. ambigua, suggesting that DNA methylation patterns can vary between generations experiencing different predation environments.…”
Section: Inheritance Mechanismssupporting
confidence: 78%
See 1 more Smart Citation
“…A similar result was observed in mice, where only the gene expression patterns of female offspring were impacted by maternal exposure to predator-cues (St-Cyr and McGowan, 2015). Interestingly, Hales et al (2017) observed a decrease in the number of differentially expressed genes between the F1 and F2 generations-a trend consistent with the observed decrease in transgenerational responses ( §4.2; Walsh et al, 2015) and the lability of inherited epigenetic marks (Fallet et al, 2020). In a companion methodological paper, Schield et al (2016) found shifts in the methylation state of sampled loci between F0 (with predator-cues) and F1 (without predatorcues) in D. ambigua, suggesting that DNA methylation patterns can vary between generations experiencing different predation environments.…”
Section: Inheritance Mechanismssupporting
confidence: 78%
“…Although this is not evidence of transgenerational epigenetic inheritance, it suggests that predation-risk driven behavior of fathers may influence the epigenetic programming of their offspring, which might in turn be transmitted to the next generation. To our knowledge, how and to what extent the epigenome is related to phenotype across generations is still an open question both in predator-prey systems and in general (see Fallet et al, 2020 for a detailed discussion). Taken together, the above results highlight the need for future work examining predator-induced TGP and WGP simultaneously, at both the (epi)genomic and phenotypic levels.…”
Section: Inheritance Mechanismsmentioning
confidence: 99%
“…These proposals are not mutually exclusive. Transgenerational inheritance has gained interest over the last years [171], notably in marine species [50,172,173], and including sea bass [83]. Parents and/or the germline were unfortunately not sampled in this study for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An early epigenetic study in molluscs using methylation‐sensitive polymerase chain reaction (PCR) and bisulphite sequencing revealed extensive CpG methylation in Crassostrea gigas (Gavery & Roberts, 2010). To date, epigenetic studies in molluscs have predominantly involved methylation analyses, often studying developmental effects (Fallet et al ., 2020), although other mechanisms include remodelling of chromatin structure through chemical changes to histone proteins and regulation by small RNA molecules. Thus, epigenetic effects may result from a mix of mechanisms in natural environments (Suarez‐Ulloa et al ., 2015).…”
Section: Shell Morphology: Genetic Adaptation and Phenotypic Plasticitymentioning
confidence: 99%